You are on page 1of 25

Section 1.

2 29 Conditional and Biconditional

Section 1.2:
1.2: Conditional and Biconditional Connectives

Purpose of Lesson: To introduce the conditional and biconditional connectives


and various equivalent forms.

The Conditional
Conditional Sentence
The most important way to combine sentences in mathematics is the
implication which has the form “if P then Q.” In a
conditional sentence (or implication),
purely logical sense, conditional sentences do not necessarily imply a cause
and effect between the components P and Q, although in mathematics and in
general discourse they do. From a logical point of view the sentence

If 1 + 1 = 3 then pigs can fly

is a legitimate implication, although there is no relationship between the


component parts. On the other hand, when we write

If N is an integer, then 2N is an even integer

there is a definite cause and effect between the components. The reader has
seen conditional sentences in Euclidean geometry where much of the subject
is explained through implications. The sentence “If a polygon has three sides,
then it is a triangle,” is a conditional sentence.

Conditional Sentence : If P and Q are sentences, then the conditional sentence


“if P then Q” is denoted symbolically by

P⇒Q
and the truth values of the sentence are defined by the truth table:

P Q P⇒Q
T T T ⇒ is false if
T F F T ⇒ F and
F T T otherwise true
F F T

The sentence P is called the assumption


assumption (or premise or antecedent
antecedent)
ntecedent of the
1
implication and Q is called the conclusion (or consequent ).

1
In pure logical systems P and Q are generally called the antecedent and consequent. In mathematics they
are more likely to be called the assumption and conclusion.
Section 1.2 30 Conditional and Biconditional

The conditional statement P ⇒ Q can be visualized by the Euler (or Venn)


Venn
diagram as shown in Figure 1.

Euler Diagram for P ⇒ Q


Figure 1

Example 1: Conditional Sentences

The following sentences are (true) conditional sentences.

i) If f is a real-valued differentiable function on ( −∞, ∞ ) , then f is continuous on


( −∞, ∞ ) .
ii) If N is an even number greater than 2, then N is the sum of two primes. (This
is true and you get an A for the course if you can prove this. Just slide your
solution under my door.)

iii) If a and b are the lengths of the legs of a right triangle, and c is the length of
the hypotenuse, then c 2 = a 2 + b 2 .

Understanding the Conditional Sentence: The conditional sentence “if P then


Q“ is best understood as a promise, where if the promise is kept, the
Section 1.2 31 Conditional and Biconditional

conditional sentence is true, otherwise the sentence is false. As an illustration


suppose your professor makes you the promise:

If pigs fly, then you will receive an A for the course.

Think about this for a second. If pigs really do fly and your professor gives
you an A, your professor has kept his or her promise and the conditional
sentence “if …. then” is true. But, suppose pigs fly but your professor
reneges and you do not get an A. Then your professor has broken the bond
and the sentence “if … then” is false.

Now (here is where it gets confusing) suppose pigs don’t fly, then what
should your professor do? In this case the professor can do anything he or
she so desires and the promise is still kept, the argument being that the
sentence “if … then” is true since the professor only promised an A if in fact
pigs fly2. This line of reasoning jives with the truth table for the conditional
sentence.

The conditional sentence P ⇒ Q is sometimes called an inference,


inference and we say
that P implies Q. Another way of stating P ⇒ Q in English is to say that P is
a sufficient condition for Q, which means the truth of P guarantees the truth of
Q. We can also say Q is a necessary condition for P, meaning that Q
necessarily follows from P.

Example 2: Necessary Conditions and Sufficient Conditions.

P Q Condition
Q is necessary for
being pregnant being female
P
2N is an
N is an integer P is sufficient for Q
integer
Q is necessary for
life on earth air
P
Getting run over by a steam
squashed P is sufficient for Q
roller
Necessary Conditions and Sufficient Conditions
Table 1

Converse, Inverse, and Contrapositive

The implication P ⇒ Q gives rise to three related implications

2
Some people might argue that if pigs don’t fly and the professor gives the student an A, then the
sentence “if … then” should be considered false.
Section 1.2 32 Conditional and Biconditional

Implication Converse Inverse Contrapositive


P⇒Q Q⇒P ∼ P ⇒∼ Q ∼ Q ⇒∼ P

It is not difficult to show by truth tables that

converse: P⇒Q ≡ Q⇒ P
inverse: P ⇒ Q ≡ ∼ P ⇒∼ Q
contrapositive: P ⇒ Q ≡ ∼ Q ⇒ ∼ P

Martin Note: Ad agencies often use the technique of equating an implication


with its (non equivalent) converse for the purpose of selling products. For
example, the slogan “Buy U.S. Olympic accredited sports gear, the designated
gear of the U.S. Olympic team, is an attempt to get you to buy into the
converse argument that if you wear accredited Olympic gear, then you have
some status as an Olympic athlete. You can think of a thousand other
advertisements that use this basic principle.

Martin Note: In mathematics when one writes the implication P ⇒ Q one


generally assumes that the sentence is true since we have assumed a true
assumption P and have proven that the conclusion Q is true. In formal logic
however, one allows for the possibility that P may be either true or false.

Martin Note: True can’t imply false, but false can imply anything.

Law of the Syllogism

A fundamental principle of logic, called the law of the syllogism, states:

“if P implies Q, and Q implies R, then P implies R”

which is equivalent to proving that

( P ⇒ Q ) ∧ ( Q ⇒ R )  ⇒ P ⇒ R

is a tautology. We can verify this by noting all the T’s in column (5) of the truth table:

(1) ( 2) ( 3) ( 4) (5)
P Q R P⇒Q Q⇒R P⇒ R ( P ⇒ Q ) ∧ ( Q ⇒ R )  ⇒ P ⇒ R
( P ⇒ Q ) ∧ (Q ⇒ R )
Section 1.2 33 Conditional and Biconditional

T T T T T T T T
T T F T F F F T
T F T F T T F T
T F F F T F F T
F T T T T T T T
F T F T F T F T
F F T T T T T T
F F F T T T T T
Table 2

Biconditional
Theorems of the form “P if and only if Q” are highly valued in
mathematics, giving equivalent and interesting new ways to say exactly the same
thing. For example, here is biconditional from number theory you may not be aware
of: A positive integer n is divisible by 3 if and only if the sum of the digits of n is
divisible by 3.

This leads us to the following definition.

Definition: If P and Q are sentences, then the biconditional sentence “ P if and


only if Q” is denoted by
P⇔Q
whose truth values are given by the truth table

P Q P⇔Q
⇔ is true if
T T T P and Q are
T F F
the same, otherwise
F T F
false
F F T

P ⇔ Q is often read as " P if and only if Q " or P iff Q for shorthand.


Another phrasing of P ⇔ Q is P is a necessary and sufficient condition for Q.

Note: Possibly the most famous conditional statement of all time is due
to the French philosopher/mathematician Rene Decartes (1591-1650)
with his famous quote in Latin “Cogito ergo sum”, which means “I think
therefore I am”, which in more traditional conditional, but less elegant
form, would be “If I think then I am.”
Section 1.2 34 Conditional and Biconditional

Example 3: Biconditional Equivalent to two Implications


Show that the biconditional P ⇔ Q is equivalent to ( P ⇒ Q ) ∧ ( Q ⇒ P ) .
Solution The truth values in the truth table under ( 5 ) and ( 6 ) are the same
as seen in Table 3.

(1) ( 2) ( 3) ( 4)
P Q P⇒Q Q⇒P ( P ⇒ Q ) ∧ (Q ⇒ P ) P⇔Q
T T T T T T
T F F T F F
F T T F F F
F F T T T T
Equivalence of ( P ⇒ Q ) ∧ (Q ⇐ P ) ≡ P ⇔ Q
Table 3

Warning Be careful not to confuse the biconditional connective P ⇔ Q with


Warning:
P ≡ Q which says P and Q are logical equivalent compound sentences. The
biconditional P ⇔ Q does not necessarily mean P and Q have the same truth
values (since the biconditional can be false), whereas P ≡ Q does.

Margin Note:
Note British mathematicians George Boole (1815-1664) and Augustus
DeMorgan (1806-1871) started a renaissance of logic in the mid-1800s. De
Morgan’s major contributions to logic include De Morgan’s laws. George
Boole approached logic in a new way, reducing it to simple algebra, replacing
the truth value T by 1 and the truth value F by 0. Logical “and” becomes
multiplication and logical “or” becomes addition in this new system. The
result was Boolean algebra, the mathematical foundation for much of digital
computers.

Example 4: Truth Values of Biconditional Sentences

Biconditional Truth Value


1 + 3 = 5 if and only if 3 + 1 = 5 True
The moon is round iff the earth is round True
d t
e = tet
1 + 2 = 3 if and only if False
dt
A necessary and sufficient condition for 1 = 0 is 6 / 3 = 2 False

In mathematics, the biconditional is stated in a variety of ways.

Equivalent Forms of the Biconditional


Section 1.2 35 Conditional and Biconditional

The following are examples of the biconditional sentence.

Equivalent Biconditional Forms


Forms Example
P⇔Q x − 1 = 0 iff x = 1
P if and only if Q x − 1 = 0 if and only if x = 1
P iff Q x − 1 = 0 iff x = 1
If P then Q and conversely if x − 1 = 0 then x = 1 and conversely
If Q then P and conversely If x = 1 then x − 1 = 0 and conversely
P is a necessary and sufficient condition for Q x − 1 = 0 is a necessary and sufficient condition for x = 1
Q is a necessary and sufficient condition for P x = 1 is a necessary and sufficient condition for x − 1 = 0

Although the two conditionals P ⇒ Q and Q ⇒ P we do have the following


equivalent conditionals

P⇒Q ≡ ∼Q⇒ ∼ P

which can be verified by constructing a truth table for each conditional. An example
of this equivalence would be

If it rains then the grass gets wet is equivalent to If grass does not get wet then it does
not rain.

Note: Greek philosophers called Modus Ponens the valid argument that if P is
true and if P ⇒ Q is true, then Q is true, which in sentential logic notation is
 P ∧ ( P ⇒ Q )  ⇒ Q .

Example 6 Biconditional Proposition in Differential Equations

Biconditional sentences allow one to replace one mathematical fact with


another. For example, we solve the first-order linear differential equation by
using a series of “if and only if” statements. We apologize to those students
who have yet to take calculus, but nevertheless the demonstration shows how
problems can be solved by a sequence of “if and only if” statements.
Section 1.2 36 Conditional and Biconditional

dy  dy 
+ ay = 0 ⇔ e at  + ay  = 0
dt  dt 
d ( e at y (t ) )
⇔ =0
dt
at
⇔ e y (t ) = c
⇔ y (t ) = c e− at

Note: The origin of the “iff” notation first appeared in print in 1955 in the text
General Topology by John Kelly although its invention is generally credited to
the Hungarian/American Paul Halmos.
Section 1.2 37 Conditional and Biconditional

Problems 1.2 Conditional and Biconditional Connectives

Working Definitions: The following definitions are needed in some problems


in this and if following sections.
▪ An integer n divides an integer m (and we write n m ) if there exists
an integer q such that m = n × q .

▪ An integer n is even if there exists an integer k such that n = 2k .

▪ An integer n is odd if there exists an integer k such that n = 2k + 1 .

▪ A natural number p is prime if it is only divisible by 1 and itself.

1. Identify the assumption and conclusion in the following conditional


sentences and tell if the implication is true or false.

a) If pigs fly then I am richer than Bill Gates.

Ans: Assumption: pigs fly, Conclusion: I am richer than Bill Gates, True

b) If a person got the plague in the 17th century they were in trouble.

Ans: Assumption: a person got the plague in the 17th century


Conclusion: they were in trouble, True

c) If you miss class over 75% of the time you are in trouble.

Ans: Assumption: you miss class over 75% of the time, Conclusion: you are in
trouble, True

d) If x is a prime number then x 2 is prime too.

Ans: Assumption: x is a prime number Conclusion: x 2 is prime too, False

e) If x and y are prime numbers, then so is x + y .

Ans: Assumption: x and y are prime numbers Conclusion: x + y is prime, False

f) If the determinant of a matrix is nonzero, the matrix has an inverse.

Ans: Assumption: If the determinant of a matrix is nonzero, Conclusion: the


matrix has an inverse, True
Section 1.2 38 Conditional and Biconditional

g) If f is a 1-1 function then f has an inverse.

Ans: Assumption: f is a 1-1 function, Conclusion: f has an inverse, True

2. Write the contrapositive of the conditional sentences in Problem 1..

Ans:

a) If I am not richer than Bill Gates, then pigs do not fly.

b) If people in the 17th century were not in trouble, then they never got the
plague.

c) If you are not in trouble, then you did not miss class 75% of the time.

d) If x 2 is not prime, then x is not prime.

e) If x + y is not prime, then either x is not prime or y is not prime.

f) If a matrix does not have an inverse, then the determinant of the matrix is
zero.

g) If f does not have an inverse, then f is not a 1-1 function.

3. Let P be the sentence "4 > 6" , Q the sentence "1 + 1 = 2" , and R the
sentence "1 + 1 = 3" . What is the truth value of the following sentences?

a) P∧∼ Q Ans: F
b) ∼ ( P ∧ Q) Ans: T
c) ∼ ( P ∨ Q) Ans: F
d) ∼ P ∧ ∼ Q Ans: T
e) P ∧ Q Ans: F
f) P ⇒ Q Ans: T
g) Q ⇔ R Ans: F
h) P ⇒ (Q ⇒ R ) Ans: T
i) ( P ⇒ Q) ⇒ R Ans: F
j) ( R ∨ Q ∨ R) ⇔ ( P ∧ Q ∧ R) Ans: F

4. Let P be the sentence “Jerry is richer than Mary”, Q is the sentence “Jerry
is taller than Mary”, and R is the sentence “Mary is taller than Jerry.” For the
Section 1.2 39 Conditional and Biconditional

following sentences what can you conclude about Jerry and Mary if the
sentences are true. Express the information in a convenient form.

a) P∨Q

Ans: Either P is true or Q is true (or both are true).

b) P ∧Q

Ans: Both P and Q are true.

c) ∼ P∨Q

Ans: Either P is false or Q is true

d) Q∧R

Ans: Both Q and R are true.

e) ∼ Q∧ ∼ R

Ans: Both Q and R are false.

f) P ∧ ( P ⇒ Q)

Ans: Both P and Q are true.

g) P ⇔ (Q ∨ R )

Ans: Either all P,Q,R are true or P is false and one (or both) Q and R are
false.

h) Q ∧ (P ⇒ R)

Ans: Either all P,Q,R are true or Q is false and P is true and R false.

i) P∨Q∨ R

Ans: Either one of P,Q,R are true.

j) P ∨ ( Q ∧ R )
Section 1.2 40 Conditional and Biconditional

Ans: Either P is true or both Q and R are true.

5. Construct truth tables to show the following sentences mean the same
thing.

a) P iff Q means the same as ∼ P iff ∼ Q

Ans:

P Q P ⇔Q ∼P ∼Q ∼ P ⇔∼ Q
T T T F F T
T F F F T F
F T F T F F
F F T T T T

b) ∼ ( P ⇔ Q ) means the same as ( P ∧ ∼ Q ) ∨ ( ∼ P ∧ Q )

Ans:

P Q P ⇔Q ∼ ( P ⇔ Q) ∼P ∼Q P∧ ∼ Q ∼ P ∧Q ( P∧ ∼ Q ) ∨ ( ∼ P ∧ Q )
T T T F F F F F F
T F F T F T T F T
F T F T T F F T T
F F T F T T F F F

c) P ⇒ Q means the same as ∼ P ∨ Q

Ans:

P Q P ⇒Q ∼P ∼ P∨Q
T T T F T
T F F F F
F T T T T
F F T T T

6. Translate the given sentences in English to conditional form.


Section 1.2 41 Conditional and Biconditional

a) Unless you study you won’t get a good grade.

Ans: If you do not study, then you will not get a good grade, or its
Ans:
contrapositive, which states: if you did get a good grade then you
studied.

b) “Do you like it? It’s yours.”

Ans: If you like it, then it is yours.

c) Come here and I’ll help you.

Ans: If you come here, then I’ll help you.

d) Get out or I’ll call the cops.

Ans: If you do not get out, then I will call the cops. (Normally one drops the
“then” in normal conversation.)

e) Anyone who doesn’t study deserves to flunk.

Ans: If anyone does not study, then they deserve to flunk.

f) Criticize her and she will slap you.

Ans: If you criticize her, (then) she will slap you. (Often people drop the
“then.”)

g) With his toupee on the professor looks younger.

Ans: If the professor wears his toupee, he looks better.

7. (In Plain English)


English Without making a truth table, say why the following are
true.

a) ( P ∨ Q ) ∧ ∼ P  ⇒ Q

Ans:
Ans If we know that P or Q but that P is not true, then we have no choice
but to assume Q is true.

b) P ∧ Q ∧ ∼ Q  ⇒ ∼ P
( )
 
Section 1.2 42 Conditional and Biconditional

Ans:
Ans If by assuming P and from this you deduce a contradiction, then you
must assume your assumption P is false.

c) ( P ∨ Q) ⇒ (∼ P ⇒ Q)
Ans: P ∨ Q says that P or Q is true. Hence, if P is not true then Q must be
true.

8. (Distributive Laws for AND and OR) For the sentences P, Q and R verify
the distributive laws

a) P ∧ (Q ∨ R) ≡ ( P ∧ Q) ∨ ( P ∧ R)
Ans: Note that the columns ( 2 ) and ( 5 ) are the same.

(1) ( 2) ( 3) ( 4) (5)
P Q R Q∨ R P ∧ (Q ∨ R) P ∧Q P∧R ( P ∧ Q) ∨ ( P ∧ R)
T T T T T T T T
T T F T T T F T
T F T T T F T T
T F F F F F F F
F T T T F F F F
F T F T F F F F
F F T T F F F F
F F F F F F F F

b) P ∨ (Q ∧ R) ≡ ( P ∨ Q) ∧ ( P ∨ R)
Ans: Note that the columns ( 2 ) and ( 5 ) are the same.

(1) ( 2) ( 3) ( 4) (5)
P Q R Q∧R P ∨ (Q ∧ R) P∨Q P∨ R ( P ∨ Q) ∧ ( P ∨ R)
T T T T T T T T
T T F F T T T T
T F T F T T T T
T F F F T T T T
F T T T T T T T
F T F F F T F F
F F T F F F T F
F F F F F F F F
Section 1.2 43 Conditional and Biconditional

9. (Inverse, Converse, and Contrapositive) One of the following sentences has


the same meaning as P ⇒ Q . Which one is it?

inverse : ∼ P ⇒ ∼ Q
converse : Q ⇒ P
contrapositive : ∼ Q ⇒ ∼ P

For the two sentences which are not always true, give examples where they
are true.

10. (True or False?) Is the following statement ever true? Is it ever false?

( P ⇒ Q ) ∧ Q  ⇒ P

Ans: From the truth table

(1) ( 2) ( 3)
P Q P ⇒Q ( P ⇒ Q) ∧ Q ( P ⇒ Q ) ∧ Q  ⇒ P
T T T T T
T F F F T
F T T T F
F F T F F

the statement is TRUE when P is true, otherwise false. Hence, the statement
is not a tautology or a contradiction.

11. Show the equivalence of the following implications.

a) P ⇒ Q (direct form of an implication)


b) ∼ Q ⇒ ∼ P (contrapositive form)
c) ( P ∧ ∼ Q ) ⇒ ∼ P (proof by contradiction)
d) ( P ∧ ∼ Q ) ⇒ Q (proof by contradiction)
e) ( P ∧ ∼ Q ) ⇒ R ∧ ∼ R (proof by reduction ad absurdum)
Ans:
Ans Draw truth tables

(
12. (Hmmmmmmmmmm) Is the statement ( P ∨ Q ) ⇔ P ∨ ∼ Q true for all )
truth values of P and Q , or is it false for all values, or is it sometimes true and
sometimes false?
Section 1.2 44 Conditional and Biconditional

Ans:
Ans It is true then P is true and Q is false, otherwise the statement is false
as can be seen from the truth table.

(1) ( 2) ( 3) ( 4)
P Q P∨Q ∼Q P ∨∼Q ( P ∨ Q) ⇔ ( P ∨ ∼ Q)
T T T F T T
T F T T T T
F T T F F F
F F F T T F

13. (
(Interesting Biconditional) Is the statement ( P ∨ Q ) ⇔ ∼ P ∨ ∼ Q true )
for all truth values of P and Q , or is it false for all values, or is it sometimes
true and sometimes false?

Ans It is true when exactly one of P and Q is true, and false when both are
Ans:
true or both are false as can be seen from the truth table.

(1) ( 2) ( 3) ( 4) (5)
P Q P∨Q ∼P ∼Q ∼P ∨∼Q ( P ∨ Q) ⇔ (∼ P ∨ ∼ Q)
T T T F F F F
T F T F T T T
F T T T F T T
F F F T T T F

14. Find the negation of the following sentences.

a) ( P ∨ Q) ∧ R
Ans: ∼ ( P ∨ Q ) ∧ R  ≡ ∼ ( P ∨ Q ) ∨ ∼ R ≡ ( ∼ P ∧ ∼ Q ) ∨ R

b) ( P ∨ Q) ∧ ( R ∨ S )
Ans: ∼ [∼ Q ⇒ ∼ P] ≡ ∼ (Q ∨ ∼ P ) ≡ ∼ Q ∧ P

c) (∼ P ∨ Q) ∧ R
Ans: ∼ ( ∼ P ∨ Q ) ∧ R  ≡ ∼ ( ∼ P ∨ Q ) ∨ ∼ R ≡ ( P ∧ ∼ Q ) ∨ ∼ R
Section 1.2 45 Conditional and Biconditional

15. Give, if possible, an example of a true conditional sentence for which

a) the contrapositive is true

Ans:
Ans If a function f is differentiable then f is continuous.

b) the contrapositive is false

Ans: The contrapositive is equivalent to the conditional so this can never


be.

c) the converse is true

Ans: If today is Monday, then it is the second day of the week. The
converse of this sentence states that if this is the second day of the week,
then it is Monday, which is also true. When both a conditional and its
converse are true the hypothesis and conclusion are logically equivalent.

d) the converse is false


Ans:
If a function f is differentiable then f is continuous. Here the converse
states that if a function is continuous, then it is differentiable, which is
false. The function f ( x ) = x is a counterexample of a continuous
function that is not differentiable.

16. The inverse of the implication P ⇒ Q is ∼ P ⇒ ∼ Q .

a) Prove or disprove that an implication and its inverse are equivalent.

Ans: Note that columns (1) and ( 4 ) are not the same. Hence the inverse
of an implication is not equivalent to the implication.

(1) ( 2) ( 3) ( 4)
P Q P ⇒Q ∼P ∼Q ∼ P ⇒∼ Q
T T T F F T
T F F F T T
F T T T F F
F F T T T T

b) What are the truth values of P and Q for which an implication and its
inverse are both true?
Section 1.2 46 Conditional and Biconditional

Ans When both P and Q are true or when they are both false.
Ans:

c) What are the truth values of P and Q for which the implication and its
inverse are both false?

Ans: They never have the same truth values.

17. For the sentence

“If N is an integer, then 2N is an even integer” write the converse,


contrapositive, and inverse sentences.

Ans Converse: If 2N is an even integer, then N is an integer.


Ans:
Contrapositive: If 2N is an odd integer, then N is not an integer.
Inverse: If N is not an integer, then 2N is not an even integer.

18. Let P,Q, and R be sentences. Show

a) P ⇒ ( Q ⇔ R ) requires paranthesis

Ans: One simply verifies that the truth tables for P ⇒ ( Q ⇔ R ) and
(Q ⇒ P ) ⇔ R are not identical.

b) ( P ∧ Q) ∨ R requires paranthesis

Ans One simply verifies that the truth tables for ( P ∧ Q ) ∨ R and
Ans:
P ∧ ( Q ∨ R ) are not identical.

c) (∼ P ∨ Q) ⇒ R may be written ∼ P ∨ Q ⇒ R

Ans: One simply verifies the truth tables for ( ∼ P ∨ Q ) ⇒ R and ∼ P ∨ Q ⇒ R


are the same.

19. (Challenge)
(Challenge) Rewrite the sentence

P ⇒ (Q ⇒ R )

in an equivalent form in which the symbol " ⇒ " does no occur.


Section 1.2 47 Conditional and Biconditional

Ans: Since (Q ⇒ R ) ≡ ( ∼ P ∨ Q ) we can write

(
 P ⇒ ( Q ⇒ R )  ≡ ∼ P ∨ ( Q ⇒ R ) ≡ ∼ P ∨ ∼ Q ∨ R )
20. (Non Obvious Statement)
Statement) The statement

P ⇒ (Q ⇒ P )

can be read “If P is true, then P follows from any Q ” Is this a tautology,
contradiction, or does its truth value depend on the truth or falsity of
P and Q ?

Ans:
Ans Making a truth table for the sentence, we find

P Q Q⇒P P ⇒ (Q ⇒ P )
T T T T
T F T T
F T F T
F F T T

Hence, the statement is a tautology.

21. (Another Non Obvious Statement)


Statement) The statement

(Q ⇒ P ) ∨ ( P ⇒ Q )
can be read “For any two sentences P and Q , it is always true that
P implies Q or Q implies P ” Is this a tautology, contradiction, or does its true
value depend on the truth or falsity of P and Q ?

Ans:
Ans Making a truth table for the sentence, we find

P Q P⇒Q Q⇒P ( P ⇒ Q ) ∨ (Q ⇒ P )
T T T T T
T F F T T
F T F F T
F F T T T

Hence, the statement is a tautology.


Section 1.2 48 Conditional and Biconditional

22. (Three-
(Three-Valued Logic) Two-valued (T and F) truth tables were basic in
logic until 1921 when the Polish logician Jan Lukasiewicz (1878-1956) and
American logician Emil Post (1897-1954) introduced n -valued logical
systems where n is any integer greater than 1. For example, sentences in a
three-valued logic might have values True, False, and Unknown. Three-value
logic is useful in computer science in database work. The truth tables for the
AND, OR, and NOT connectives are as follows:

A B A OR B A AND B NOT A
True True True True False
True Unknown True Unknown False
True False True False False
Unknown True True Unknown Unknown
Unknown Unknown Unknown Unknown Unknown
Unknown False Unknown False Unknown
False True True False True
False Unknown Unknown False True
False False False False True

From these connectives, derive the connectives for the conditional and
biconditional connectives.

Ans: Using the fact that P ⇒ Q ≡ ∼ P ∨ Q , the conditional connective is

(1) ( 2) ( 3)
P Q ∼P ∼ P∨Q P⇒Q
T T F T T
T U F U U
T F F F F
U T U T T
U U U U U
U F U U U
F T T T T
F U T T T
F F T T T

Using the fact that p P ⇔ Q ≡ ( P ⇒ Q ) ∧ ( Q ⇒ P ) we have the biconditional in


column ( 6 ) .
Section 1.2 49 Conditional and Biconditional

(1) ( 2) ( 3) ( 4) (5) ( 6)
P Q ∼P ∼ P∨Q P⇒Q ∼Q ∼ Q∨ P Q⇒P ( P ⇒ Q ) ∧ (Q ⇒ P )
T T F T T F T T T
T U F U U U T T U
T F F F F T T T F
U T U T T F U U U
U U U U U U U U U
U F U U U T T T U
F T T T T F F F F
F U T T T U U U U
F F T T T T T T T

23. (Modus Ponens and Modus Tollens) Modus Ponens3 and Modus Tollens4
are systematic ways of making logical arguments that takes the form

If P then Q If P then Q
P ∼Q
Therefore Q Therefore ∼ P
Modus Ponens Modus Tollens

Show that Modus Ponens and Modus Tollens are both tautologies,.

Ans: Modus Ponens is a tautology which can be seen by constructiong the


truth table for ( P ⇒ Q ) ∧ P  ⇒ Q and observing there are all T’s in column
(4) below:

(1) ( 2) ( 3) ( 4)
P Q P ⇒Q ( P ⇒ Q) ∧ P ( P ⇒ Q ) ∧ P  ⇒ Q
T T T T T
T F F F T
F T T F T
F F T F T

Modus Tollens is a tautology which can be seen by constructing the truth table
for ( P ⇒ Q ) ∧ ∼ Q  ⇒ ∼ P and observing there are T’s in column (4) below:
 

3
Latin: mode that affirms.
4
Latin mode that denies.
Section 1.2 50 Conditional and Biconditional

(1) ( 2) ( 3) ( 4)
P Q P ⇒Q ∼Q ( P ⇒ Q) ∧ ∼ Q ( P ⇒ Q ) ∧ ∼ Q  ⇒ ∼ Q
 
T T T F F T
T F F T F T
F T T F F T
F F T T T T

24. (Interesting) Are the following two statements equivalent?

P ∧ (Q ⇒ R)
( P ∧ Q) ⇒ R
Ans: Yes, as can be seen from the following truth table.

(1) ( 2) ( 3) ( 4)
P Q R Q⇒R P ∧Q P ∧ (Q ⇒ R) ( P ∧ Q) ⇒ R
T T T T T T T
T T F F T F F
T F T T F T T
T F F T F T T
F T T T F F T
F T F F F F T
F F T T F F T
F F F T F F T

25. Determine which of the following statements is true for the following
diagram.
Section 1.2 51 Conditional and Biconditional

a) All the squares are red if and only if all the squares are green.
b) Either there is a green circle or there are no yellow circles.
c) If there is red circle, then there is not a green circle.

Ans:

a) Both statements “all the squares are red” and “all squares are green” are
false,so the biconditional is true.

b) There is a green circle so the disjunction is true.

c) The premise is false to the conditional is true.

26. (Logical Puzzle) On an isolated island the inhabitants either always tell the
truth or always lie. You make a visit to the island and ask the first person you
meet about their favorite baseball team. The person says two things:

▪ I like the Red Sox.


▪ If I like the Red Sox, then I like the Yankees.

Does the islander like the Red Sox? Does the islander like the Yankees?
What is the reason for your answer?
Section 1.2 52 Conditional and Biconditional

Ans: Let’s first assume the following statements are true.

R : I LIKE THE RED SOX


R ⇒ Y : IF I LIKE THE RED SOX I LIKE THE YANKEES

The only way the conditional R ⇒ Y is true when R is for Y to be false.

On the other hand, both statements

R : I LIKE THE RED SOX


R ⇒ Y : IF I LIKE THE RED SOX I LIKE THE YANKEES

can not both be false since if R is false, then the conditional R ⇒ Y will
always be true. Hence we conclude both statements R ⇒ Y and R are true.
But if both these statements are true, so is Y . In other words, the islander
likes both the Red Sox and the Yankees.

27. (Professor
Professor Snarf’s Birthday)
Birthday)

Professor Snarf tells Mary the month of his birthday and tells Dave the
day of his birthday, and tells them not to pass this information to the other.
Professor Snarf then tells them if they can deduce his birthday, they will each
receive an A in their logic course, knowing it is impossible. However, Professor
Snarf does not realize how smart Mary and Dave are in logic.

Day
1 2 3 4 5 6
Jan Jan 3 Jan 4 Jan 6
Feb Feb 3 Feb 5
Montth
March March 1 March 4
April April 1 April 2 April 6

After a moment’s thought:

Statement 1: Mary says, “If I don’t know the answer, then Dave doesn’t know
either.
Statement 2:
2 Dave says “I didn’t know the answer before, but now I know.”
Statement 3:
3 Mary says: “I now know the answer too.”

whereupon they correctly tell Professor Snarf his birthday and he grudgenly
gives them their As. What was the correct answer that Mary and Dave gave
Professor Snarf?
Section 1.2 53 Conditional and Biconditional

Ans: Let us rename Mary by MONTH and Dave by DAY to so we don’t forget
that MONTH knows the month and DAY knows the day.

In a nutshell, MONTH is going to pass some valuable information to DAY (enough


so DAY knows the birthday), and then DAY passes back some information to
MONTH (enough so that MONTH knows the birthday), and then MONTH passes
you the reader information so YOU know the birthday.

At the start MONTH (who knows the month but not the day) does not know the
birthday and so Statement 1, which is an implication of the form P ⇒ Q implies
that neither does DAY This is MONTH’s clever day of telling DAY that the
month is not February or April, since if the birthday were in one of those two
months, DAY would know inasmuch as day 2 only occurs in April and day 5 only
in Feb. So now MONTH and DAY reduced the number of possible birthdays from
10 to 5 as illustrated below.

Day
1 2 3 4 5 6
Jan Jan 3 Jan 4 Jan 6
Montth
March March 1 March 4

It is now DAY’s turn to deduce the answer and pass enough information back to
MONTH so she can deduce the answer. DAY says he knows the birthday, which
tells us MONTH it is not on the 4th of the month. (It is easy for him to find the
answer, he just looks in the column of the day Professor Snarf gave him to find
the month. So now we are down to three possibilities March 1, Jan 3, or Jan 6.

Day
1 2 3 4 5 6
Jan Jan 3 Jan 6
Montth
March March 1

Now, it is MONTH’s turn to deduce the birthday and tell you ! She says she
knows the birthday, which means the birthday must by March 1, otherwise if her
month was Jan she would be unable to decide between Jan 3 and Jan 6. Hence,
Professor Snarf’s birthday is March 1.